Evropeizacija ustavnosodne presoje prek Listine Evropske unije o temeljnih pravicah - Vatovec, Katarina (Dignitas (Ljubljana), 2019)
With the entry into force of the Lisbon Treaty, the EU Charter of Fundamental Rights has become a binding source of fundamental rights in the European Union. As such, it has become a tool of integrating and accelerating these rights as well as a tool of Europeanization that by its contemporary catalogue of civil, political, social, and economic rights shapes and develops the European human rights regime. The article firstly touches upon the question of when the EU Charter of Fundamental Rights is applicable in the case law of constitutional courts. Then it focuses on the use of the EU Charter of Fundamental Rights in the case law of the Slovenian Constitutional Court. By analysing the selected constitutional court decisions, the article explains how the existence of the EU Charter has influenced the Europeanization of the Slovenian Constitutional Court.
Keywords: Listina Evropske unije o temeljnih pravicah; pravno varstvo; temeljne pravice; ustavno sodstvo; ustavnosodna presoja